VALUATION AND OTHER PROBLEMS CONNECTED WITH THE STUDY OF CORPORATE PROFITS. - Epstein, Ralph C. (The Accounting Review, 1933)
In determining the investment base, several alternatives immediately occur to either the accountant or the economist. Total assets is one possibility. Total assets less intangibles is another. The sum of all items of corporate capital structure; bonded debt, capital stock and surplus and undivided profits, is a third. Still a fourth base might be the sum of capital stock and surplus, without the inclusion of funded debt. Capital assets may be stated on the basis of cost or on the basis of a valuation. Just because, in the case of any individual corporation, assets may be stated upon a cost basis or upon the basis of an appraisal, it is often believed that no valid general figures can be developed. Many small companies overvalue their property accounts. On the other hand, a number of large companies are quite conservative in their charges to depreciation, obsolescence and other reserves. If charges to depreciation are not separated from charges to other reserves, if revaluations of plant and equipment are not explained in detail in the annual report, then the task of making allowances for conservatism or extravagance in estimating such margins of error is intensified.